2013
DOI: 10.1177/0269215513478227
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transcutaneous electrical nerve stimulation on strength, proprioception, balance and mobility in people with stroke: a randomized controlled cross-over trial

Abstract: The results provide initial evidence of the potential of 'active TENS' to benefit physical function after stroke which warrants further phase II trials to develop the intervention. Concerns that stimulation could have a detrimental impact on balance and increase risk of falls were not supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 28 publications
(42 reference statements)
1
41
0
Order By: Relevance
“…In this study, high frequency current, 70-130Hz biphasic symmetrical stimulus, was used. The reason for the frequency modulation was to prevent the adaptation of sensory system (Tyson et al, 2013). The improved balance in this study is believed to be a result of the decreased spasticity and improved arrangement by the high frequent TENS.…”
Section: ⅳ Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this study, high frequency current, 70-130Hz biphasic symmetrical stimulus, was used. The reason for the frequency modulation was to prevent the adaptation of sensory system (Tyson et al, 2013). The improved balance in this study is believed to be a result of the decreased spasticity and improved arrangement by the high frequent TENS.…”
Section: ⅳ Discussionmentioning
confidence: 73%
“…This frequency modulation was for the prevention of adaptation of sensory system. The stimulus intensity was increased until subjects felt tingling or buzzing feeling in foot and ankle without any muscle contraction or radiation in proximal body segments (Tyson et al, 2013). Furthermore, the intensity was controlled three times in every 15 minute in order to prevent the adaptation.…”
Section: Designmentioning
confidence: 99%
“…They found a significant increase in cortical motor representation of all muscles in the TENS group from pre-test to post-test, and suggested the potential of sensory training by application of TENS in neurorehabilitation (Meesen et al 2011). A recent study by Tyson et al (2013) reported that application of TENS had positive effects on strength, proprioception, balance, and mobility in stroke survivors by providing supplementary sensory stimulation. In a randomized controlled study, Tekeoğlu et al (1998) reported on the effectiveness of TENS on the level of activities of daily living (ADL) of stroke patients after an eight-week intervention period, and suggested that TENS can be an effective additional method in regaining motor functions and improving ADL in hemiplegic patients.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it appears that electrical somatosensory stimulation is sufficient for modulation of reorganization of the motor cortex during performance of the required motor task, which may be beneficial to improvement of motor function in stroke rehabilitation (Golaszewski et al 1999;Ridding et al 2000;Ng and Hui-Chan 2007). There are a variety of electrical stimulators; however, unlike functional electrical stimulator, neuromuscular electrical stimulation, or interferential current therapy, transcutaneous electrical nerve stimulation (TENS) is relatively easy to apply and control, readily available, risk free, and inexpensive, particularly if the stimulation is applied at a pleasant sensory level (Laufer and Elboim-Gabyzon 2011;Tyson et al 2013). Based on previous studies, we hypothesized that additional benefit could be attained if task-related training was used with TENS in upper arm rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS) is used as an adjunct treatment to enhance paretic lower‐limb muscle strength,1, 2, 3 walking speed,3, 4, 5, 6 balance performance,2, 3, 7 and functional mobility1, 5, 7, 8 in subjects with acute,1 subacute,6, 7 and chronic2, 4, 5 stroke. The therapeutic effects of TENS may be mediated via peripheral9, 10, 11 and central mechanisms 12, 13.…”
Section: Introductionmentioning
confidence: 99%